Cross‐sectional evaluation of periodontal inflammation and oral hygiene status between fixed appliances and Invisalign in patients affected by craniofacial anomalies. Issue 2 (5th December 2022) - Tortora, Chiara; Poli, Corinne; Suriano, Alice; Panzeri, Maria C.; Autelitano, Luca; Meazzini, Maria C.
Abstract: Objective: The objective of this cross‐sectional study was to compare the difference in the oral health status and oral hygiene of orthodontic treatment with aligners (AL) and with fixed appliances (FA) in patients affected by craniofacial anomalies (CFA). Materials and Methods: The sample consisted of 100 Caucasian patients affected by various CFA from two different hospitals. Fifty patients treated with AL were matched for sex, age and CFA with a control sample of 50 patients treated with FA. Patients' periodontal conditions were evaluated in both samples. O'Leary Plaque Control Record, bleeding on probing (BOP) and DMT/dmft Index were evaluated in both samples. Results: The FA group presented an O'Leary Plaque Control Record of 60% ± 30, while AL presented an O'Leary Plaque Control Record of 40% ± 29.7 ( p ‐value = 0.02), BOP was 22.1% ± 14 in FA and 12% ± 0.13 in AL ( p ‐value = 0.03). The DMFT/dmft was not statistically different ( p ‐value = 0.13). p ‐value was set at <0.039. Conclusion: The study shows that the sample with FA presented a higher O'Leary Plaque Control Record and BOP compared to the AL sample. AL might, therefore, be an interesting alternative to FA in patients with CFA, who generally have a lower level of oral hygiene.